PCR-DGGE Analysis of Caecal Microflora of NatustatTM-Supplemented Turkeys Challenged with Histomonas meleagridis - Waters, Sinéad.M; Duffy, Cepta F.; Power, Ronan F.G. (International Journal of Poultry Science, 2005)
Histomoniasis is a disease of turkeys on litter or range caused by the fragile protozoan Histomonas meleagridis, a parasite of worms, primarily spread in faeces, in Heterakis gallinarum (caecal worm) eggs or in Eisenia foetita (earthworms). Symptoms include poor feed conversion ratio (FCR), decreased body weight (BW), diarrhea, caecal and liver lesions, darkening of the facial regions and sometimes death. Nitarsone can be used as an aid in the prevention of histomoniasis. NatustatTM (Alltech, Inc., Nicholasville, KY), a proprietary plant derived product, is a natural alternative for the prevention of histomoniasis disease in poultry. In this trial, NatustatTM, was used at 1.925kg/Tonne and compared with nitarsone at 0.1875kg/Tonne in male Hybrid turkey diets to 42 d of age on histomonad infected litter from broiler breeders. Infected and uninfected, non-supplemented control groups were also included. On d 28, 35 and 42 of the trial, 16 birds from each group were euthanized. Caecal contents were removed, lyophilized and pooled by group for each sampling day. These samples were subjected to a molecular culture-independent methodology; polymerase chain reaction combined with denaturing gradient gel electrophoresis (PCR-DGGE), to identify shifts in caecal microbial populations between the different dietary supplemented groups. The similarity index, Sorenson`s pairwise similarity coefficient was used to compare caecal PCR-DGGE profiles to each other. In addition sequence analysis was performed on PCR-DGGE bands of interest. Resultant sequences were analyzed using the Basic Local Alignment Search Tool (BLAST) sequence analysis package online at the National Centre for Biotechnology Information (NCBI) homepage http://www.ncbi.nlm.nih.gov. Notable shifts in the PCR-DGGE profiles were observed between the controls and the supplemented groups. It was concluded that PCR-DGGE profiles could be used to monitor bacterial constituents of caecal contents, indicating that NatustatTM has the ability to manipulate the composition of the intestinal microflora.